Enhanced Dendritic Actin Network Formation in Extended Lamellipodia Drives Proliferation in Growth-Challenged Rac1(P29S) Melanoma Cells - Mohan, Ashwathi S. (Dev Cell, 2019)
Actin assembly supplies the structural framework for cell morphology and migration. Beyond structure, this actin framework can also be engaged to drive biochemical signaling programs. Here, we describe how the hyperactivation of Rac1 via the P29S mutation (Rac1(P29S)) in melanoma hijacks branched actin network assembly to coordinate proliferative cues that facilitate metastasis and drug resistance. Upon growth challenge, Rac1(P29S)-harboring melanoma cells massively upregulate lamellipodia formation by dendritic actin polymerization. These extended lamellipodia form a signaling microdomain that sequesters and phospho-inactivates the tumor suppressor NF2/Merlin, driving Rac1(P29S) cell proliferation in growth suppressive conditions. These biochemically active lamellipodia require cell-substrate attachment but not focal adhesion assembly and drive proliferation independently of the ERK/MAPK pathway. These data suggest a critical link between cell morphology and cell signaling and reconcile the dichotomy of Rac1’s regulation of both proliferation and actin assembly by revealing a mutual signaling axis wherein actin assembly drives proliferation in melanoma.